Fever-Associated Seizures or Epilepsy: An Overview of Old and Recent Literature Acquisitions - Pavone, Piero; Pappalardo, Xena Giada; Parano, Enrico; Falsaperla, Raffaele; Marino, Simona Domenica; Fink, John Kane; Ruggieri, Martino (Frontiers in Pediatrics, 2022)
In addition to central nervous system infections, seizures and fever may occur together in several neurological disorders. Formerly, based on the clinical features and prognostic evolution, the co-association of seizure and fever included classical febrile seizures (FS) divided into simple, complex, and prolonged FS (also called febrile status epilepticus). Later, this group of disorders has been progressively indicated, with a more inclusive term, as “fever-associated seizures or epilepsy” (FASE) that encompasses: a) FS divided into simple, complex, and prolonged FS; b) FS plus; c) severe myoclonic epilepsy in infancy (Dravet syndrome); d) genetic epilepsy with FS plus; and e) febrile infection-related epilepsy syndrome (FIRES). Among the FASE disorders, simple FS, the most common and benign condition, is rarely associated with subsequent epileptic seizures. The correlation of FS with epilepsy and other neurological disorders is highly variable. The pathogenesis of FASE is unclear but immunological and genetic factors play a relevant role and the disorders belonging to the FASE group show to have an underlying common clinical, immunological, and genetic pathway. In this study, we have reviewed and analyzed the clinical data of each of the heterogeneous group of disorders belonging to FASE.